Birth of the modern Chesapeake Bay estuary between 7.4 and 8.2 ka and implications for global sea-level rise - Bratton, John F.; Colman, Steven M.; Thieler, E. Robert; Seal, Robert R. (Geo-Marine Letters, 2002)
Two major pulses of sea-level rise are thought to have taken place since the last glacial maximum — meltwater pulses (mwp) 1A (12 cal ka) and 1B (9.5 cal ka). Between mwp 1B and about 6 cal ka, many of the complex coastal ecosystems which ring the world’s oceans began to form. Here we report data for rhenium, carbon isotopes, total organic carbon, and fossil oysters from Chesapeake Bay which span the transition from fresh to brackish water conditions in the bay in the mid-Holocene. These data constrain sea-level change and resulting environmental change in the bay. They indicate that the transition was rapid, and that it was produced by (1) a third pulse of rapid eustatic sea-level rise, or (2) a geometry of the prehistoric Chesapeake Bay basin which predisposed it to a nonlinear response to a steadily rising sea level. Similar nonlinear changes in vulnerable coastal environments are likely to take place in the future due to polar warming, regardless of the timing or rate of sea-level rise.
id: 540